THE INFLUENCE OF YOUTUBE CONTENT EXPOSURE ON GEN Z RELIGIOSITY IN JAVA AND SUMATRA - Rubiyanah Rubiyanah; Indah Fadhilla; Muhamad Zen (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
At the beginning of YouTube development, there were few broadcasts featuring information about religious values. But now, along with the times, many preachers are starting to use YouTube as a medium of da'wah to reach the younger generation who may not come to conventional recitations such as lectures in recitation activities. Based on this background, this study aims to measure the effects of YouTube, especially da'wah shows, on the younger generation’s religiosity at universities in Java and Sumatra. The religiosity aspect consists of Aqidah, morals, and sharia. These three aspects will be used as variables revealed to be questioned for respondents. The research method used in this study is the SEM (Structural Equation Modeling) analysis technique. Data collection in the study was conducted at four campuses: UIN Syarif Hidayatullah Jakarta, Pamulang University (UNPAM) and UIN Imam Bonjol Padang and Padang State University (UNP), with a sample of 200 students representing Gen-Z. Sampling used simple random sampling. The research results obtained a significance score of 0.031 < 0.05 so that it can be concluded; First, the preachers (YouTube) figure has little effect on the religiosity of Gen-Z, namely the preachers is only 0.019, meaning that the effect is small. On YouTube, the second theory, preaching, affects Gen-Z religiosity by 0.093, meaning that the effect is negligible. Third, the da'wah method on YouTube involves the religiosity of Gen-Z, which is equal to 0.131, which means that the method is more influential than the preacher and material. This means that the hypothesis is accepted or has a significant effect, especially on the da'wah method.